Primary Stent Placement for Hepatic Artery Stenosis After Liver Transplantation: Improving Primary Patency and Reintervention Rates. Issue 10 (25th October 2018) - Sarwar, Ammar; Chen, Christine; Khwaja, Khalid; Malik, Raza; Raven, Kristin E.; Weinstein, Jeffrey L.; Evenson, Amy; Faintuch, Salomao; Fisher, Robert; Curry, Michael P.; Ahmed, Muneeb
Abstract: Recent studies have reported high rates of reintervention after primary stenting for hepatic artery stenosis (HAS) due to the loss of primary patency. The aims of this study were to evaluate the outcomes of primary stenting after HAS in a large cohort with longterm follow‐up. After institutional review board approval, all patients undergoing liver transplantation between 2003 and 2017 at a single institution were evaluated for occurrence of hepatic artery complications. HAS occurred in 37/454 (8%) of patients. HAS was defined as >50% stenosis on computed tomography or digital subtraction angiography. Hepatic arterial patency and graft survival were evaluated at annual intervals. Primary patency was defined as the time from revascularization to imaging evidence of new HAS or reaching a censored event (retransplantation, death, loss to follow‐up, or end of study period). Primary stenting was attempted in 30 patients (17 female, 57%; median age, 51 years; range, 24‐68 years). Surgical repair of HAS prior to stenting was attempted in 5/30 (17%) patients. Endovascular treatment was performed within 1 week of the primary anastomosis in 5/30 (17%) of patients. Technical success was accomplished in 97% (29/30) of patients. Primary patency was 90% at 1 year and remained unchanged throughout the remaining follow‐up period (median, 41 months; interquartile range [IQR], 25‐86 months). Reintervention was required in 3 patients to maintain stent patency. The median time period between primary stenting and retreatment was 5.9 months (IQR, 4.4‐11.1 months). There were no major complications, and no patient developed hepatic arterial thrombosis or required listing for retransplantation or retransplantation during the follow‐up period. In conclusion, primary stenting for HAS has excellent longterm primary patency and low reintervention rates.